AUDITING OF EDUCATION ACTIVITIES IN PRE-SCHOOL EDUCATION INSTITUTIONS - Fethi TURAN (International Journal of Eurasia Social Sciences, 2016)
ABSTRACTThis research aims to examine the education activities in official and private pre-school organizations bound to National Ministry of Education in Ankara city example. This is a qualitative research relying on situation study. The universe of the study consists of official and private kindergartens in Ankara while study group consists of audit report prepared for 10 official and 10 private kindergartens obtained by simple random method. In the research education activity examination form, which was developed by researcher by taking advantage of guidance and audit forms and data was evaluated by descriptive analysis method. Although the guidance and audit guide developed according to research results fulfill many requirements as a forward step, it is understood that there are still areas which are open for development and according to audit reports it was observed that there are teacher, manager and system originated problems in conduction of education activities in kindergartens. In this case it can be suggested that pre-school education field expert academicians should play role or at least examine and share their opinions related with preparation of guidance and audit guide and also in service training activities should be planned and applied for teachers and managers in pre-school education institutions without discriminating official or private kindergartens.